Financial toxicity in insured patients with multiple myeloma: a cross-sectional pilot study. Issue 10 (October 2015) - Huntington, Scott F; Weiss, Brendan M; Vogl, Dan T; Cohen, Adam D; Garfall, Alfred L; Mangan, Patricia A; Doshi, Jalpa A; Stadtmauer, Edward A
Summary: Background: Financial toxicity is increasingly recognised as adversely affecting the quality of life and medication adherence in patients with cancer in the USA. Patients with multiple myeloma might be particularly vulnerable because of high use of novel treatments and extended treatment duration. Methods: Between Aug 18, 2014, and Jan 7, 2015, we did a cross-sectional survey of individuals receiving at least 3 months of ongoing treatment for multiple myeloma at a tertiary academic medical centre in the USA. The survey was derived from previous reported studies and included the 11-item COST measure (financial toxicity score range 0–44). A paper survey was offered to eligible patients on arrival for routine follow-up visits, and participants were asked to complete the survey before or after their visit to the clinic. Insurance and treatment data were obtained from patients' electronic health records. Findings: Of 111 patients approached for the study, 100 individuals completed the survey. 59 (59%) of 100 patients reported that treatment costs were higher than expected, 70 (71%) of 99 had at least minor financial burden, and 36 (36%) of 100 reported applying for financial assistance. Use of savings to pay for myeloma treatment was common (43 [46%] of 94 patients) and 21 (21%) of 98 individuals borrowed money to pay for medications. COST scores were highly correlated with patient-reported use of strategies to cope with myeloma treatment expenses. On multivariable analysis, younger age (correlation coefficient β 0·36, 95% CI 0·15 to 0·56, p=0·00092), non-married status (5·6, 1·5 to 9·6, p=0·0074), longer duration since diagnosis (−4·8, −9·3 to −0·2, p=0·042), and lower household income (US40 000–79 999: 7·8, 2·7 to 12·9, p=0·0031; ≥80 000: 11·8, 7·1 to 16·4, p<0·0001) were associated with higher financial burden as measured with the COST score. Interpretation: Patient-reported financial toxicity and use of coping mechanisms were common in our insured population with multiple myeloma. Additional attention to rising treatment costs and cost sharing is needed to address the increasing evidence of financial toxicity affecting patients with cancer. Funding: University of Pennsylvania Perelman School of Medicine.